Liver and cardiovascular mortality after hepatitis C virus eradication by DAA: Data from RESIST‐HCV cohort. Issue 8 (7th May 2021) - Calvaruso, Vincenza; Petta, Salvatore; Cacciola, Irene; Cabibbo, Giuseppe; Cartabellotta, Fabio; Distefano, Marco; Scifo, Gaetano; Di Rosolini, Maria Antonietta; Russello, Maurizio; Prestileo, Tullio; Madonia, Salvatore; Malizia, Giuseppe; et al.
Abstract: Real‐world evidence on the course of Hepatitis C Virus (HCV) chronic liver disease after Sustained Virologic Response (SVR) obtained with direct‐acting antiviral drugs (DAAs) are still limited, and the effects on mortality remain unclear. We evaluated the post‐treatment survival of 4307 patients in the RESIST‐HCV cohort (mean age 66.3 ± 11.6 years, 56.9% males, 24.7% chronic hepatitis, 66.9% Child‐Pugh A cirrhosis and 8.4% Child‐Pugh B cirrhosis) treated with DAAs between March 2015 and December 2016 and followed for a median of 73 weeks (range 16–152). Proportional cause‐specific hazard regression for competing risks was used to evaluate the survival and to assess the predictors of liver and cardiovascular death. Overall, 94.7% of patients achieved SVR while 5.3% were HCV RNA‐positive at last follow‐up. Sixty‐three patients (1.4%) died during the observation period. SVR was associated with a decreased risk of liver mortality (hazard ratio, HR0.09, beta −2.37, p < .001). Also, platelet count (HR 0.99, beta‐0.01, p = .007) and albumin value (HR 0.26, beta −1.36 p = .001) were associated with liver mortality by competing risk analysis. SVR was associated with a reduced risk of cardiovascular mortality regardless of presence of cirrhosis (HR 0.07, beta‐2.67, p < .001). Presence of diabetes (HR 3.45, beta 1.24, p = .014) and chronic kidney disease class ≥3 (HR 3.60, beta 1.28, p = 0.016) were two factors independently associated with higher risk of cardiovascular mortality. Patients with SVR to a DAA therapy have a better liver and cardiovascular survival, and the effects of HCV eradication are most evident in patients with compensated liver disease.